Strength performance of banana fiber ash as cementitious material with different temperature - Nur Aqilah , Abd Karim (2014)
Concrete is one of the materials that is widely used in construction all around the world. This material is widely used because it has several benefits such as, more durable, energy-efficient, low maintenance, affordability, fire-resistance, excellent thermal mass and also versatility. This research was conducted to determine the optimum temperature and strength of concrete to produce good cementitious material by using banana fiber ash. Agriculture waste material can help to increase the strength of concrete. The source of natural fibre are found in plant and they are readily environmental friendly and cheap. In addition, natural fiber ash has an excellent potential to improve the performance of concrete. In this study, compressive strength test was conducted to know the strength of concrete with three different temperatures. Banana trunk is cut layer by layer and bum in furnace with three different temperatures that is 400°C, 500°C, and 600°C. A total of 27 cubes with 1 OOmm x 1 OOmm x 100mm were used to determine the strength of concrete using banana fiber ash. All this specimens is cure for 7 days, 14 days and 28 days using water curing method. 2% of banana fiber ash was replaced with cement by weight. The materials use in this study was banana fibre ash, sand, cement, coarse aggregate, and water. The result analysis shows, The higest temperature obtain in this research was by burned banana ash with 500°C. while the lowest temperature was 600°C when the concrete was curing for 28 days. The lowest the temperature the higher the strength of concrete can be obtained.